Framework for Assessing the Performance of Hierarchical Organizations in Adoption Of higher Education Information System - Haerani, Reni; T.K.A, Rahman; Fatah, Anwar (2024)
Adopting and successfully implementing information systems in higher education is essential to improve administrative processes and communication and support academic activities. However, the hierarchical nature of these organizations poses unique challenges that need to be addressed for the effective adoption of information systems. This study proposes a framework for assessing the performance of hierarchical organizations in effectively implementing information systems in universities. This framework provided a structured approach to assessing the performance of hierarchical organizations in the adoption of information system success in higher education institutions. This framework considered the various dimensions influencing the successful adoption of information systems in hierarchical organizations. This dimension includes leadership support, communication channels, organizational culture, and resource allocation. This study aimed to provide a structured approach for evaluating and adopting information systems at various levels of the organizational hierarchy. A structural equation model using a quantitative method and Smart Partial Least Square are utilized for data analysis. Using a population of 121 respondents, data was collected using a questionnaire instrument used the Google Form link Banten Province higher education leadership level. Secondary data was obtained using documentation studies and literature studies. The limitations of this study are limited by a small sample size, making it challenging to generalize findings to a broader population of higher education institutions. Further, organizational culture plays a vital role in the adoption of technology. The framework may need to sufficiently address the influence of cultural factors on the acceptance and performance of information systems within hierarchical organizations. The research results show that by leveraging this framework, institutions can enhance their information system adoption processes and ultimately improve their effectiveness in utilizing information systems for academic and administrative purposes.